2022
DOI: 10.5009/gnl210217
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Opportunistic Infection in Inflammatory Bowel Disease Patients in Asia: A Questionnaire-Based Multicenter Study

Abstract: Background/Aims: Opportunistic infection in inflammatory bowel disease (IBD) has become a serious problem. However, its status of doctors' opinions and test equipment in hospitals are unclear. The aim of the study was to investigate these issues to improve the prognosis of IBD patients.Methods: This retrospective, multicenter study was conducted by 83 investigators who were members of the Asian Organization for Crohn's and Colitis. Data on opportunistic infection were collected from hospital databases between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This online questionnaire survey recruited a large number of Asian physicians, more than half of whom were gastroenterologists specializing in IBD, suggesting that the survey findings reflect real-world clinical settings in these Asian countries/regions. Moreover, in contrast to a previous study based on questionnaires administered to IBD investigators [ 48 ], the present study included a large number of Asian physicians from various countries. This present finding may also offer insights into the management of infectious complications in Asian patients with IBD that are distinct from those observed in Western patients with IBD [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This online questionnaire survey recruited a large number of Asian physicians, more than half of whom were gastroenterologists specializing in IBD, suggesting that the survey findings reflect real-world clinical settings in these Asian countries/regions. Moreover, in contrast to a previous study based on questionnaires administered to IBD investigators [ 48 ], the present study included a large number of Asian physicians from various countries. This present finding may also offer insights into the management of infectious complications in Asian patients with IBD that are distinct from those observed in Western patients with IBD [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, frequent, long-term, and combined use of immunosuppressive agents can lead to critical clinical issues, such as opportunistic infections, in IBD patients. 3 , 8 - 12 …”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Yang et al [ 8 ] also investigated infectious complications in Asian patients with IBD using a questionnaire survey. They found that most physicians considered tissue cytomegalovirus (CMV) DNA as an index for the diagnosis of CMV colitis.…”
mentioning
confidence: 99%